Topical Application of Paraboea leuserensis on Excision Wound with Angiogenesis and Vascular Endothelial Growth Factor Analysis - Heryani, Dyah Wijiana; Maya Wardhani, Fiska; Yensuari; Nazimuddin Putri, Nadya; Nardi, Leo; Ikhtiari, Refi (HAYATI Journal of Biosciences, 2024)
Gagatan harimau or Paraboea leuserensis B.L. Burtt is an endemic plant that grows in limestone areas, natively found in Leuser Mountain Area, North Sumatra Province, Indonesia. This study determines the wound healing potential of P. leuserensis gel-based ethanolic extract (PGEE) on full-thickness excision wounds based on the angiogenesis and VEGF expression. Here, we reported 67 compounds detected by LC-MS/MS from the ethanolic extract. The antibacterial activity regarding pathogenic wound infection was also investigated. The experimental study used 30 Rattus novergicus, randomly divided into five treatment groups: base gel as a negative control, Bioplacenton as a positive control, PGEE 2.5%, 5%, and 10%. Experimental data showed that PGEE indicated a significant effect on bacterial inhibition (p = 0.02), where the greatest inhibitory was found against S. epidermidis. Topical application of PGEE showed significant differences in the number of blood vessels of PGEE 2.5% and 10% (p = 0.007) and expression of VEGF (p<0.05). The correlation between the number of blood vessels and VEGF was also described with the number of macrophages, fibroblasts, collagen, and wound diameter. Overall, this study demonstrates the pharmacological potential of PGEE for wound healing applications regarding angiogenesis and VEGF expression.